More than just shopping: Ethnic majority consumers and cosmopolitanism in immigrant grocery shops. Issue 7 (19th May 2018) - Parzer, Michael; Astleithner, Franz
ABSTRACT: This paper explores ethnic majority consumption practices in immigrant economies. Drawing on recent debates on cosmopolitanism, we focus on the question of how the use of immigrant shops by members of the ethnic majority is intertwined with the erosion and/or the (re)production of symbolic boundaries. We conducted 31 in-depth interviews and 15 go-alongs with consumers in immigrant grocery shops in Vienna. Our findings show how consumption is based upon and shaped by the various ways consumers attribute meaning to the shops, the products on offer as well as their shopping experiences. We identified five different types of consumption: consuming nostalgia, consuming patronage, consuming change, consuming alterity and consuming diversity . However, we only consider the latter two as cosmopolitan consumption in a narrower sense. We show that within these types, the expression of openness towards 'the other' constitutes a form of cultural capital displayed by members of the privileged classes. The article argues in favour of a more comprehensive understanding of consumption practices in immigrant economies. This encompasses that not every act of shopping in immigrant businesses is cosmopolitan and that research is called to consider that the various types of consumption effect boundaries along ethnicity and class in manifold ways.